CAMTA3 negatively regulates disease resistance through modulating immune response and extensive transcriptional reprogramming in cassava. (24th July 2020) - Chang, Yanli; Bai, Yujing; Wei, Yunxie; Shi, Haitao
Abstract: As one of the important crops in the world, cassava production is seriously threatened by Xanthomonas axonopodi s pv. manihotis ( Xam ) all year round. Calmodulin-binding transcription activators (CAMTAs) play key roles in biotic stress and abiotic stress in plants, however, their roles in cassava remain elusive. In this study, six MeCAMTAs were identified, and MeCAMTA3 with the highest induction upon Xam infection was confirmed as a transcription factor that binds to the vCGCGb motif. MeCAMTA3 negatively regulates plant disease resistance against Xam . On the one hand, MeCAMTA3 negatively regulated endogenous salicylic acid and reactive oxygen species accumulation, pathogenesis-related genes MePRs' transcripts and callose deposition during cassava- Xam interaction but not under control conditions. On the other hand, RNA sequencing showed extensive transcriptional reprogramming by MeCAMTA3, especially 18 genes with a vCGCGb motif in the promoter region in hormone signaling, antioxidant signaling and other disease resistance signaling. Notably, chromatin immunoprecipitation-polymerase chain reaction showed that eight of these genes might be directly regulated by MeCAMTA3 through transcriptional repression. In summary, MeCAMTA3 negatively regulates plant disease resistance against cassava bacterial blight through modulation of multiple immune responses during cassava- Xam interaction and extensive transcriptional reprogramming.